Nursing process applied to an older adult with periprosthetic fracture on the right hip - Isaí Arturo Medina Fernández; Perla Noemi Polanco Tinal; Reyna Torres Obregón; Sandra Cecilia Esparza González (CuidArte)
Periprosthetic fracture is a rare complication in elderly adults of total arthroplasties and hip revision. Objective. To provide comprehensive care through the nursing care process to an older adult with periprosthetic fracture of the right hip. Methodology. Nursing care process carried out in the area of joint reconstruction of a third level hospital in Mexico City, Mexico; An assessment was applied based on Marjory Gordon’s functional patterns and comprehensive geriatric assessment; data were extracted from the electronic clinical record. The nursing process was applied to the three priority diagnoses according to the NANDA, NOC and NIC taxonomies. Results. During hospitalization, the main nursing diagnoses identified were acute pain, deterioration of physical mobility and risk of peripheral neurovascular dysfunction, nursing interventions were aimed at the control of immobility, activity and exercise, as well as pain management, precautions in embolism and lower limb monitoring. Conclusion.  during the intervention period, the older adult had a slow improvement, however, there were no changes in the prioritization of nursing diagnoses.